Analysis of Acceptance and Use of the MyKopay Application Using the UTAUT 2 and EUCS Models - Zahrati, Wenty; La Ode Muh. Rabil Saputra; Zahra Aqilah Dytihana (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The government of Payakumbuh City introduced the MyKopay application through the Department of Communication and Information as a means to provide public services and information related to local government activities. This study aims to analyze the acceptance and use of the MyKopay application using two models: the Unified Theory of Acceptance and Use of Technology (UTAUT 2) and End-User Computing Satisfaction (EUCS). Additionally, it seeks to identify aspects of the application that need improvement and maintenance. The research method is descriptive quantitative. The research findings indicate that factors such as Content, Accuracy, Format, Timeliness, Ease of Use, Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit, and User Satisfaction do not have a significant positive impact on User Satisfaction or Behavioral Intention. However, Behavioral Intention has been proven to have a significant positive effect on Use Behavior. Age and gender factors strengthen the Habit variable and have a significant positive impact on Use Behavior. The research results show that the MyKopay application has been accepted and used by the people of Payakumbuh City